Study of Refractive Errors on School going Children in North West Zone of Bangladesh (TAJ: Journal of Teachers Association, 2018)
Refractive error is one of the most common cases of visual impairment around and it is quite common among the children but neglected. Children of age 5-15 years constitute a large portion of the country population. If the refractive errors may not corrected lead to reduced vision (amblyopia) and strabismus. Main ophthalmic problem in children is refractive errors and maximum children live in rural area of Bangladesh but a few studies on such ground had been carried out previously. Therefore it is matter of investigation in this ground. As such study of refractive error of age 5-15 years of low health facilitated area like Chapainawabgonj district situated in the North West Zone of Bangladesh have been considered in this study. On basis of the collected 500 samples the prevalence of refractive error has been computed and it was found to be 9.2% which is similar with the existing study.TAJ 2016; 29(1): 1-6